A Study to Assess the Knowledge and Practice Regarding Prevention of TB Among Staff Nurses Working in a Selected TB Hospital at Jodhpur - Shyam Sunder (International Journal of Community Health Nursing And Practices, 2026)
Tuberculosis (TB) remains a major global public health concern, causing significant morbidity and mortality, particularly among healthcare workers. Staff nurses are at heightened risk due to repeated exposure to patients with active TB, making knowledge and adherence to preventive practices critical. The present study was conducted to evaluate the knowledge and practices of staff nurses concerning tuberculosis (TB) prevention at Kamla Nehru TB and Chest Hospital, Jodhpur. A descriptive and non-experimental research design was employed, involving 40 staff nurses who were chosen through a non-probability convenience sampling technique. Data collection was carried out using two tools: a structured knowledge questionnaire and an observational checklist. The questionnaire included 30 multiple-choice items to measure knowledge, while the checklist comprised 15 statements designed to assess nurses’ TB prevention practices. Scoring criteria categorize knowledge and practice levels as inadequate, moderate/average, or adequate/good. Content validity of the tools was established by nine experts in medical-surgical nursing, and reliability was confirmed using the split-half method, yielding coefficients of r = 0.84 for the knowledge questionnaire and r = 0.82 for the observational checklist. Data analysis involved descriptive statistics, t-tests to assess correlations, and Chi-square tests to determine associations between demographic variables and knowledge/practice levels. The study highlights the critical role of staff nurses in TB control and emphasizes the need for ongoing education, training, and adherence to infection control measures to prevent occupational TB. Findings from this research can guide healthcare institutions in developing strategies to enhance TB prevention among nursing staff, ensuring both workforce safety and improved patient outcomes.
Keywords: Knowledge; TB prevention; and practices; infection control; staff nurses; tuberculosis (TB)